1989
DOI: 10.1002/pssa.2211130226
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dislocations on the performance of 3 to 5 μm Hg1–xCdxTe graded gap photoresistors

Abstract: Numerical calculations of detectivity of photoresistors made of graded gap n‐type Hg1–xCdxTe structures are carried out. The model involves a generalized approach, taking into account position‐dependent and wavelength‐dependent material parameters, absorption coefficient, band‐to‐band recombination mechanism, and recombination mechanism associated with misfit dislocations present in the graded gap layers. The last mentioned recombination process reduces considerably the carrier lifetime and the photoresistor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our investigations of the pin-photodetector electrophysical characteristics and parameters show that the impurity composition and imperfection most significantly affect the amplification factor, dark current, and quantum yield [7]. In these cases, the minor charge-carrier lifetime is inversely dependent on the dislocation density τ p = 15/N, where N is measured in cm -2 , whereas the recombination rate is proportional to the dislocation density irrespective of the dislocation type [8]. It is found that no decrease in the density of uniformly distributed screw dislocations improves the operating parameters of pinphotodetectors, while the edge dislocations in silicon affect those parameters due to changes in µ and in the concentration of the dopant.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Our investigations of the pin-photodetector electrophysical characteristics and parameters show that the impurity composition and imperfection most significantly affect the amplification factor, dark current, and quantum yield [7]. In these cases, the minor charge-carrier lifetime is inversely dependent on the dislocation density τ p = 15/N, where N is measured in cm -2 , whereas the recombination rate is proportional to the dislocation density irrespective of the dislocation type [8]. It is found that no decrease in the density of uniformly distributed screw dislocations improves the operating parameters of pinphotodetectors, while the edge dislocations in silicon affect those parameters due to changes in µ and in the concentration of the dopant.…”
Section: Resultsmentioning
confidence: 88%
“…The calculations show that R = 0.046 µm for E D = (E V + 0.6) eV [8] and f = 0.05. Thus, µ gd = 17 m/(V⋅s) at high dislocation density N = 10 12 m -2 , m * = 0.56 m 0 , and v = 1.56·10 5 m/s.…”
Section: Resultsmentioning
confidence: 93%
“…J h = qJ hP h (8) Many papers devoted to the solution of these equations have been published from papers of Gumme115 and De Mari 1G down to recently commercially available numerical programs. 17,18 Results from some additional papers 12,19,2° have also been partially regarded in the present paper.…”
Section: Theoretical Modelmentioning
confidence: 99%